A Drosophila model to study retinitis pigmentosa pathology associated with mutations in the core splicing factor Prp8 - Dimitrije Stanković; Ann-Katrin Claudius; Thomas Schertel; Tina Bresser; Mirka Uhlirova (The Company of Biologists, 2020)
Retinitis pigmentosa (RP) represents genetically heterogeneous and clinically variable disease characterized by progressive degeneration of photoreceptors resulting in a gradual loss of vision. The autosomal dominant RP type 13 (RP13) has been linked to the malfunction of PRPF8, an essential component of the spliceosome. Over 20 different RP-associated PRPF8 mutations have been identified in human patients. However, the cellular and molecular consequences of their expression in vivo in specific tissue contexts remain largely unknown. Here, we establish a Drosophila melanogaster model for RP13 by introducing the nine distinct RP mutations into the fly PRPF8 ortholog prp8 and express the mutant proteins in precise spatiotemporal patterns using the Gal4/UAS system. We show that all nine RP-Prp8 mutant proteins negatively impact developmental timing, albeit to a different extent, when expressed in the endocrine cells producing the primary insect moulting hormone. In the developing eye primordium, uncommitted epithelial precursors rather than differentiated photoreceptors appeared sensitive to Prp8 malfunction. Expression of the two most pathogenic variants, Prp8S>F and Prp8H>R, induced apoptosis causing alterations to the adult eye morphology. The affected tissue mounted stress and cytoprotective responses, while genetic programs underlying neuronal function were attenuated. Importantly, the penetrance and expressivity increased under prp8 heterozygosity. In contrast, blocking apoptosis alleviated cell loss but not the redox imbalance. Remarkably, the pathogenicity of the RP-Prp8 mutations in Drosophila correlates with the severity of clinical phenotypes in patients carrying the equivalent mutations, highlighting the suitability of the Drosophila model for in-depth functional studies of the mechanisms underlying RP13 etiology. This article has an associated First Person interview with the first author of the paper.